Plasma disinfection and the deterioration of surgical tools at atmospheric pressure plasma - Siti Khadijah, Zaaba; Akitsu, Tetsuya; Ohkawa, Hiroshi; Katayama-Hirayama, Keiko; Tsuji, Masao; Shimizu, Naohiro; Imanishi, Yuichirou (The Institute of Electrical Engineers of Japan, 2010)
Link to publisher's homepage at http://www.iee.or.jp/index-eng.html